Strategi Investasi Milenial Dalam Mengelola Portofolio Keuangan di Era Digital - Mahrani, Luthfiyah; Jasman, Jumawan; Dewintari, Putri (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
This study aims to formulate appropriate investment strategies for managing financial portfolios among the millennial generation. The method used in this research is SWOT analysis (Strengths, Weaknesses, Opportunities, Threats), combined with the IFAS (Internal Factor Analysis Summary) and EFAS (External Factor Analysis Summary) matrices to identify internal and external factors that influence millennials' investment decisions. Data were collected through questionnaires and indicator weighting by determining the IFAS and EFAS matrices, involving 83 respondents who are actively using digital platforms for investment, within the millennial age range of 28–43 years. Data processing was conducted using SPSS (Statistical Program for Social Science). The results of the analysis show that enhancing financial literacy knowledge is fundamental for investment, especially for millennials who often make decisions without fully considering the associated risks and benefits. The use of technology, alongside rapid technological development, has significantly facilitated access to various types of information and helped individuals define their investment goals more clearly.